A new, mesophotic Coryphopterus goby (Teleostei, Gobiidae) from the southern Caribbean, with comments on relationships and depth distributions within the genus - Carole C. Baldwin; D. Ross Robertson (ZooKeys, 2015)
A new species of western Atlantic Coryphopterus is described from mesophotic depths off Curaçao, southern Caribbean. Coryphopterus curasub sp. n., is similar to C. dicrus in, among other features, having two prominent pigment spots of roughly equal intensity on the pectoral-fin base, the pelvic fins fused to form a disk, and no pelvic frenum. The two species can be differentiated by body depth (shallower in C. curasub at origin of dorsal fin and caudal peduncle); differences in the pigmentation on the head, trunk, and basicaudal region; and usually by total number of rays (spinous plus soft) in the second dorsal fin (10–11, usually 11, in C. curasub, 10 in C. dicrus). Coryphopterus curasub differs from other Coryphopterus species that have a prominent pigment spot on the lower portion of the pectoral-fin base (C. punctipectophorus and C. venezuelae) in, among other features, lacking a pelvic frenum. Coryphopterus curasub was collected between 70 and 80 m, the deepest depth range known for the genus. Collections of C. venezuelae at depths of 65–69 m extend the depth range of that species by approximately 50 m. Mitochondrial cytochrome c oxidase subunit I (COI) data corroborate the recognition of C. curasub as a distinct species but do not rigorously resolve its relationships within the genus. A revised key to the western Atlantic species of Coryphopterus is presented.